Enhancement of in vitro antitumour activity of epirubicin in HER2+ breast cancer cells using immunoliposome formulation - Farnaz Khaleseh; Abbas Hemmati Azandaryani; Fatemeh Fathian Kolahkaj; Mozafar Khazaei; Katayoun Derakhshandeh (IET Nanobiotechnology)
Abstract Epirubicin (EPI) is one of the potent breast cancer (BC) chemotherapeutic agents, but its adverse effects limit its efficacy. Herein, EPI was selected to be loaded in liposomal carrier, which has been targeted by a monoclonal antibody, Herceptin. The preparation process of liposomes was a modified ethanol injection method followed by Herceptin conjugation. The in vitro cell toxicity and cellular uptake of optimum formulation against HER2+ and HER2− cancer cell lines were evaluated. The results showed that the drug loading (DL%) and encapsulation efficiency (EE%) of liposome preparation method yielded 30.62% ± 0.49% and 62.39% ± 8.75%, respectively. The average size of naked liposomes (EPI‐Lipo) and immunoliposomes (EPI‐Lipo‐mAb) was 234 ± 9.86 and 257.26 ± 6.25 nm, with a relatively monodisperse distribution, which was confirmed by SEM micrographs. The release kinetic followed Higuchi model for both naked and immunoliposomes. In vitro cytotoxicity study on three different BC cell lines including BT‐20, MDA‐MB‐453 and MCF‐7 demonstrated higher toxicity of EPI in the Herceptin conjugated form (EPI‐Lipo‐mAb) in comparison with the free EPI and EPI‐Lipo in HER2 overexpressing cell line. In addition, the cellular uptake study showed a higher uptake of immunoliposomes by MCF‐7 cells in comparison with naked liposomes. In conclusion, these data show that the targeted delivery of EPI to breast cancer cells can be achieved by EPI‐Lipo‐mAb in vitro, and this strategy could be used for breast cancer therapy with further studies.